Assessment of hazards and risks associated with dietary exposure to mineral oil for the Belgian population. (March 2021) - Mertens, Birgit; Van Heyst, Annelies; Demaegdt, Heidi; Boonen, Imke; Van Den Houwe, Kathy; Goscinny, Séverine; Elskens, Marc; Van Hoeck, Els
Abstract: Recently collected dietary exposure data on mineral oil saturated (MOSH) and aromatic (MOAH) hydrocarbons were used to evaluate the risks associated with exposure to mineral oil through food for the Belgian population. For MOSH, the no observed adverse effect level (NOAEL) value of 19 mg kg −1 bw day −1 based on the hepatic inflammation-associated granulomas found in a 90-day oral study in F-344 rats was used as point of departure (PoD). Due to existing toxicological uncertainties, the margin of exposure (MOE) approach was applied. In all investigated scenarios, the MOE values were well above 100, indicating that there is no direct health concern related to MOSH exposure for the Belgian population. Nevertheless, more appropriate risk assessment approaches for MOSH based on adequate PoD are needed. For dietary exposure to MOAH, which are potentially genotoxic and carcinogenic, no MOE values could be calculated due to the lack of adequate dose-response carcinogenicity data. In two investigated worst-case scenarios, a health concern related to MOAH exposure could not be excluded, highlighting that more data are needed to perform an adequate risk assessment. The possibility to use in vitro bioassays to collect such additional toxicological information for MOAH present in food samples was also investigated. Highlights: Risk assessment based on realistic dietary mineral oil exposure data. MOE values for MOSH were above 100 in all investigated exposure scenarios. More appropriate risk assessment approaches for MOSH are required. More toxicological data needed to evaluate risks of dietary MOAH exposure. No clear link between endocrine/genotoxic effects in bioassays and MOSH/MOAH.